Correlation of Antifungal Activities and Nonribosomal Peptide Synthetase Gene Expression of Bacillus siamensis 1021 - Warinya Nuwong; Chokchai Kittiwongwattana (Chiang Mai Journal of Science, 2022)
Members of the genus Bacillus were biocontrol agents against various phytopathogenic fungi. Several factors affected the regulation and production of nonribosomal peptides (NRPs) in Bacillus species. The aim of this study was to examine how culture media infl uenced the antagonistic activities and gene expression of Bacillus siamensis 1021. The bacterial supernatant from potato dextrose broth (PDB) exhibited higher inhibitory effects against mycelia of Pyricularia oryzae and Colletotrichum fructicola, when compared with those from nutrient broth (NB) and minimal salt medium (MSM). However, the biocontrol activities of these supernatants were not signifi cantly different when they were tested against P. oryzae and C. fructicola conidia. Additionally, the bacterial supernatant from PDB signifi cantly reduced the disease severity caused by P. oryzae in rice seedlings when compared with the water-treated control group. The genome of strain 1021 was sequenced, and biosynthetic gene clusters of nonribosomal peptides surfactin, fengycin and bacillibactin were identifi ed. Effects of PDB, NB and MSM media on expression levels of core biosynthetic genes of surfactin (srfAA), fengycin (fenC) and bacillibactin (dhbE) gene clusters were determined by reverse-transcription quantitative PCR. fenC expression was signifi cantly increased in PDB and corresponded with the antagonistic activities against fungal mycelia. Conversely, expression of the regulatory genes comA and codY in PDB were highly reduced in PDB, indicating their negative relation with fenC expression. This expression analysis indirectly suggested that fengycin was potentially the bioactive compound of B. siamensis 1021 against P. oryzae and C. fructicola
Keywords: Plant-Microbe Interactions and Immunity; Probiotics and Fermented Foods; Antimicrobial Peptides and Activities